Acoustic Field Prediction Method and Simulation Research Based on Acoustic Field Geometric Average Theory. Issue 1 (1st March 2023) - He, Xianwen; Li, Zhizhong; Sun, Junping
Abstract: In order to meet the capability requirements of submarine radiated noise acoustic field prediction in free field and improve the detection and anti-detection capabilities, this paper proposes an acoustic field prediction method based on the geometric average theory of acoustic field. According to the measured self-noise information, a global search method is used. By calculating the average energy of the spherical, the extended compensation for different point distances is achieved, so as to predict the radiation noise at different distances. Through simulation experiments, it is found that the method proposed in this paper has a fast calculation speed, and the acoustic field prediction accuracy is high.